Study on CCB (Chromated Copper Boric Acid) DipPreservation of Golpata (Nypa fruticans) - Ilias, G. N. M.; Rahman, Md Ashiqur; Hannan, Md. Obaidullah; Feroz, S. M.; Abdullah, Faridah (Universiti Putra Malaysia Press, 2002)
Golpata (Nypa fruticans) is a cheap source of roof thatches in Bangladesh. However, its short life span of 2-3 years makes it unsuitable for long-term use. This study was carried out to investigate the treatability of Golpata by dipping in CCB (Chromated Copper Boric acid) mixture. Samples of leaves and midribs of Golpata with moisture contents ranging from 16.63% to 70.67% at the start of the experiment, were dipped into CCB solution of four different concentrations for 2, 4, 6 and 8 hours and examined for CCB penetration and retention. Penetration was determined by using a copper and boron indicator whereas retention was calculated by X-ray spectroscopy. Results revealed that two factor chemical (CCB) concentrations and duration of dipping period have considerable effect on the preservation of Golpata but not the moisture content. Better CCB penetration was observed after 6 hours of dipping time in both leaves and midribs but better CCB retention was found for both 6 and 8 hours dipping time for both specimen types respectively. Treatment time showed a significant effect at 5% level of confidence. Chemical (CCB) concentration had a significant effect on penetration of Golpata leaves but had no effect on the retention.